Combined Use of HArmonyCa and Hyaluronic Acid Fillers: A Holistic Approach to Facial Rejuvenation - Sadiye Kus, MD; Sukran Sarigul Guduk, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The multifactorial nature of aging necessitates a comprehensive assessment addressing contour, volume, and facial laxity, and a holistic treatment plan. We evaluated combined use of HArmonyCa with HA fillers to improve laxity and overall aesthetic outcomes. A detailed guide is also presented regarding facial shapes, special areas, and volume needs. Methods:. This retrospective case series evaluates 10 patients’ facial laxities with Facial Laxity Rating Scale using 2-dimensional before and after photographs (posttreatment and 6-month mark). Overall improvement was assessed by the investigator and patients by comparing to baseline. Patient satisfaction was measured with a questionnaire. Results:. The Facial Laxity Rating Scale scores (jowl and neck) were highest at baseline and lowest at 6-month mark. Facial laxity significantly improved over time for jowl (P < 0.001) and neck (P = 0.007). At the sixth month, facial laxity significantly improved compared with baseline both in jowl (P = 0.001) and neck (P = 0.011). Global Aesthetic Improvement Score evaluations improved significantly during the 6-month period (P < 0.001). Global Aesthetic Improvement Score was significantly higher at 6-month posttreatment compared with immediate posttreatment evaluation (P < 0.001). Patients were satisfied immediately after treatment and 6 months after. The satisfaction significantly improved at the sixth month compared with immediately after treatment (P = 0.033). Conclusions:. A combined use of HArmonyCa and HA fillers improves laxity in the lower face and neck and enhances aesthetic outcomes with high patient satisfaction. Overall improvement and patient satisfaction are higher at the sixth month, which is attributable to biostimulation.